6th World Congress of the World Society for Pediatric Infectious Diseases (WSPID). (March 2010) - Dinleyici, Ener Cagri; Kurugol, Zafer
The 6th World Congress of the World Society for Pediatric Infectious Diseases (WSPID) was held in Buenos Aires, Argentina between 18 and 22 November, 2009. This is one of the biggest pediatric infectious disease assemblies in the world and it brought together pediatricians and pediatric infectious disease and vaccine experts. Numerous topics about pediatric infectious diseases were discussed during the congress. The scientific program focused on vaccines and vaccine-preventable diseases, including epidemiological and vaccine efficacy trials and updates on topics of childhood infectious disease. We summarize the current knowledge about some childhood vaccines and vaccine-preventable diseases, including rotavirus vaccines, conjugated pneumococcal vaccines (PCV-7, PHiD-CV and PCV-13), varicella, pertussis meningococcal and pandemic H1N1 vaccines. The next WSPID congress will be held in Melbourne, Australia between 16 and 20 November 2011.